2016
DOI: 10.1089/hum.2016.015
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Gene Transfer of a Hexosaminidase Variant Using an scAAV9.47 Vector Corrects GM2Gangliosidosis in Sandhoff Mice

Abstract: GM2 gangliosidosis is a group of neurodegenerative diseases caused by β-hexosaminidase A (HexA) enzyme deficiency. There is currently no cure. HexA is composed of two similar, nonidentical subunits, α and β, which must interact with the GM2 activator protein (GM2AP), a substrate-specific cofactor, to hydrolyze GM2 ganglioside. Mutations in either subunit or the activator can result in the accumulation of GM2 ganglioside within neurons throughout the central nervous system. The resulting neuronal cell death ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 50 publications
0
46
0
Order By: Relevance
“…This paper provides information on the development of the reagents, along with evidence supporting the hypothesis that this has a likelihood of providing a therapeutic benefit. A companion article by Osmon and colleagues, 52 in this issue of Human Gene Therapy (see p. 497), describes the application of this approach and vector design with a mouse model of SD, which does display a severe disease phenotype, and is more appropriate for evaluating treatment efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…This paper provides information on the development of the reagents, along with evidence supporting the hypothesis that this has a likelihood of providing a therapeutic benefit. A companion article by Osmon and colleagues, 52 in this issue of Human Gene Therapy (see p. 497), describes the application of this approach and vector design with a mouse model of SD, which does display a severe disease phenotype, and is more appropriate for evaluating treatment efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Several papers have described a variety of studies of gene therapy applied to the brain of small and larger animal models of GM2 gangliosidoses, mostly using AAV vectors [ 4 ]. Early gene therapy studies for GM2 gangliosidoses were based on the intracranial co-administration of AAV1 or AAVrh8 vectors carrying the α and β subunits on SD mice [ 153 , 154 ] or cats [ 82 , 155 , 156 , 157 ]. These results showed a wide distribution of the enzyme through the brain, a significant increase in the life spam, the reduction of GM2 ganglioside levels, and an improvement on motor functions [ 82 , 155 , 156 , 157 , 158 , 159 ].…”
Section: Current Proposals For the Treatment Of Gm2 Gangliosidosesmentioning
confidence: 99%
“…Moreover, treated SD cats showed an increase on the myelin-enriched cerebrosides and a decrease in the microglial activation, suggesting an attenuation of the neuroinflammation [ 79 , 160 ], which is an important physiopathology feature observed in GM2 patients [ 73 , 80 , 84 ]. As an alternative to the multi-vector injections, a self-complementary AAV9.47 vector was evaluated, which encoded for a hybrid µ subunit (HexM) that combine the α-subunit active site, the stable β-subunit interface, and unique areas of each subunit necessary for the interaction with the GM2AP [ 40 , 154 ]. The results showed that HexM was able reduce the GM2 ganglioside storage in thalamus, hypothalamus, and hippocampus; and led to an improvement on animal behavior [ 154 ].…”
Section: Current Proposals For the Treatment Of Gm2 Gangliosidosesmentioning
confidence: 99%
See 1 more Smart Citation
“…In SD patients, an excessive accumulation of undegraded substrates, including GM2 ganglioside, is observed, particularly within lysosomes in the neuronal cells, due to the deficiencies of HexA and HexB, which leads to neurological symptoms in the central nervous system (CNS), such as mental retardation, spasms and quadriplegia. SD model mice (SD mice), established by means of Hex β-subunit gene disruption, exhibit the accumulation of GM2 gangliosides throughout the CNS and the abnormalities in motor functions, which are quite similar to those observed in SD patients Several therapeutic approaches for SD have been investigated for decades, including substrate reduction therapy [4][5][6] , bone marrow transplantation 7,8 , stem cell therapy 9,10 , enzyme replacement therapy [10][11][12][13][14] , gene therapy [15][16][17] and chaperon therapy 18 , where the aim is to reduce the accumulated substrates. However, the disease remains incurable.…”
Section: Sandhoff Diseasementioning
confidence: 99%